2012
DOI: 10.1177/1082013211428218
|View full text |Cite
|
Sign up to set email alerts
|

Textural, physicochemical and sensory properties compensation of fat replacing in pork liver pâté incorporating emulsified canola oil

Abstract: Saturated animal fat was replaced in pork pâté with pre-emulsified canola in a 3% sodium caseinate/0.5% xanthan gum solution in order to obtain a stable oily phase. Fat was replaced with different proportions of emulsified canola oil. The inclusion of emulsified oil in pâté enhanced cocking yield and moisture but increased fluids release. Nonetheless, total fat content remained practically constant, meaning no detrimental effect on caloric content. Replacing 50% of lard with emulsified oil did not affect color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
25
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 42 publications
5
25
1
1
Order By: Relevance
“…Therefore, we might conclude that the b* parameter was the only one significantly affected by fat replacement by olive oil in pâté. These outcomes are in disagreement with those reported by Morales-Irigoyen et al (2012) as to lightness and redness, since they found significant changes (P<0.05) in these parameters when fat was substituted by emulsified canola oil. However, our findings in yellowness are similar to those reported by them.…”
Section: Physico-chemical Parameterscontrasting
confidence: 99%
See 4 more Smart Citations
“…Therefore, we might conclude that the b* parameter was the only one significantly affected by fat replacement by olive oil in pâté. These outcomes are in disagreement with those reported by Morales-Irigoyen et al (2012) as to lightness and redness, since they found significant changes (P<0.05) in these parameters when fat was substituted by emulsified canola oil. However, our findings in yellowness are similar to those reported by them.…”
Section: Physico-chemical Parameterscontrasting
confidence: 99%
“…Choi et al (2009) also reported significantly different results (P<0.05) among all batches in the partial replacement of animal fat with various vegetable oils emulsified with dietary fiber extracted from rice bran in the manufacture of a cooked batter made of pork ham. Nevertheless, in this case, lightness and yellowness showed a different behavior regarding values observed by Morales-Irigoyen et al (2012), which increased and decreased respectively. The differences in color parameters may be due to differences between the oils (canola vs. olive oil) used in each study.…”
Section: Physico-chemical Parametersmentioning
confidence: 53%
See 3 more Smart Citations